Would you like your Internet with or without video? - William Lehr; Douglas Sicker (International Telecommunications Society (ITS), 2016)
According to Cisco's VNI forecast, "consumer Internet video traffic will be 85 percent of all consumer Internet traffic in 2020, up from 76 percent in 2015," and the majority of this traffic will be entertainment-oriented video. Many might view this as the (near) realization of the promised convergence of digital broadband delivery platforms that has been coming since first generation broadband services started becoming available in the mid-1990s. A question we should ask is whether this is the Internet we want? Even if one concludes that the marriage between entertainment media and the Internet is a foregone conclusion, it is worthwhile to consider what this may mean for the design, regulation, and economics of the Internet. In this paper, we critically examine the proposition that the conventional wisdom that convergence toward “everything over IP,” or even stronger, “everything over the Internet,” is efficient, inevitable, or desirable may be wrong. Convergence means different things in technical, economic, and policy terms. Building a single network that is optimized for 80% entertainment video traffic might disadvantage other services. Moreover, the economics of media entertainment are distinct from, and potentially in conflict with, the economics motivating many of the usage cases most often cited as justification for viewing the Internet as an essential infrastructure. Finally, separately managing the traffic for Internet and video services may be advantageous in addressing regulatory agenda items such as performance measurement, set-top boxes, universal service, OVD reclassification, and Internet interconnection. While most of the traffic may share the same physical (principally, wired) conduit into homes, it may be more efficient and flexible to segregate traffic into multiple logically distinct networks; and doing so may facilitate technical, market, and regulatory management of the shared resources.
Keywords: 330